Water Quality Monitoring System Using IOT - Priyanka Phadke; Komal Pawar; Tanpure Pratiksha; Prof. Salunkhe S.V; Dr. Divekar S.N (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents a water quality monitoring system based on the Internet of Things (IoT). The system is designed to measure critical water parameters such as turbidity, temperature, and TDS sensor using sensor networks. The collected data is transmitted in real-time to a Thing Speak platform for further analysis and visualization. The system aims to provide continuous water quality monitoring, improving decision-making for water resource management. The research includes hardware and software implementations, ensuring a cost-effective and scalable solution. Water quality monitoring is a crucial aspect of environmental sustainability, public health, and industrial safety. Traditional methods involve manual sampling and laboratory analysis, which are time-consuming, costly, and inefficient for continuous monitoring. To overcome these limitations, this paper presents an Internet of Things (IoT)-based water quality monitoring system that enables real-time analysis of essential water parameters, including turbidity, temperature, and total dissolved solids (TDS). The system leverages sensor networks and cloud computing to provide automated and scalable solutions for efficient water resource management.